Enhancing Financial Management Capabilities through Management and Accounting Training - Luther Hasan Lase; Ristanto (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2026)
Financial management capability is a fundamental determinant of organizational sustainability and business performance, particularly for micro, small, and medium-sized enterprises (MSMEs) and community-based business actors. Despite its importance, many business owners continue to experience difficulties in budgeting, bookkeeping, financial reporting, cash flow management, and financial decision-making due to limited managerial and accounting competencies. Management and accounting training has therefore emerged as an effective educational intervention to improve financial literacy, strengthen managerial capabilities, and promote more accountable and transparent financial practices.This study aims to analyze the effectiveness of management and accounting training in enhancing participants' financial management capabilities, with particular emphasis on improving financial knowledge, bookkeeping skills, budgeting practices, financial reporting, and financial decision-making. This study employed a qualitative approach using a descriptive case study design. Data were collected through observations, semi-structured interviews, documentation, and participant reflections involving individuals who participated in management and accounting training programs. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation and method triangulation. The findings indicate that management and accounting training significantly improved participants' understanding of financial management principles and strengthened their practical competencies in recording transactions, preparing financial statements, budgeting, and managing business cash flows. Participants also demonstrated greater awareness of the importance of separating personal and business finances, utilizing financial information for decision-making, and implementing systematic financial control. Furthermore, the training enhanced participants' confidence in managing business finances, increased accountability, and encouraged the adoption of more structured and sustainable financial management practices